2017
DOI: 10.1362/204440817x15108539431541
|View full text |Cite
|
Sign up to set email alerts
|

Characterising marketing paradigms for sustainable marketing management

Abstract: She researches the concept of 'purpose-driven organisations'-a practitioner phenomenon focused on creating sustainable wellbeing through business success, and the role of marketing and governance in delivering this agenda. She has published research papers and thought pieces in journals including: Nature Climate Change, The New Scientist, Carbon Management and Sustainable Development. Victoria has over 15 years experience consulting in marketing and sustainability, having previously worked for Accenture with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…CBE provides guidance demonstrating how the process is applied over a development, implementation and evaluation cycle. Paradigmatic shifts are needed to encourage marketing to transition from a focus solely on profit maximization to one that enables societal wellbeing (Hurth & Whittlesea, 2017; Peattie & Peattie, 2003; Savitz, 2013). For example, a paradigm that “guides” individuals toward more sustainable needs and wants and “co-creates” solutions has been proposed to replace previous marketing models that maximized profit through “selling” or “responding” to consumer desires (Hurth & Whittlesea, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBE provides guidance demonstrating how the process is applied over a development, implementation and evaluation cycle. Paradigmatic shifts are needed to encourage marketing to transition from a focus solely on profit maximization to one that enables societal wellbeing (Hurth & Whittlesea, 2017; Peattie & Peattie, 2003; Savitz, 2013). For example, a paradigm that “guides” individuals toward more sustainable needs and wants and “co-creates” solutions has been proposed to replace previous marketing models that maximized profit through “selling” or “responding” to consumer desires (Hurth & Whittlesea, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Paradigmatic shifts are needed to encourage marketing to transition from a focus solely on profit maximization to one that enables societal wellbeing (Hurth & Whittlesea, 2017; Peattie & Peattie, 2003; Savitz, 2013). For example, a paradigm that “guides” individuals toward more sustainable needs and wants and “co-creates” solutions has been proposed to replace previous marketing models that maximized profit through “selling” or “responding” to consumer desires (Hurth & Whittlesea, 2017). Yet to realize socially or environmentally beneficial outcomes, detailed frameworks, accompanied by empirical testing of those frameworks is required.…”
Section: Discussionmentioning
confidence: 99%
“…This broad perspective makes the role of those responsible for planning, implementing and developing these goals, i.e. senior staff, company's managers as well as middle-level employees (Caruana & Chatzidakis, 2014;Hurth & Whittlesea, 2017). They should be focused not only on implementing new processes, but also on engaging lower-level employees in them.…”
Section: Organisational Context Of Creating Employee Engagement Towarmentioning
confidence: 99%
“…This is traditionally understood within the 'marketing mix' -a tool box which includes what products or services are created (Product), their cost (Price), how they are made available (Place), and how they and the identity of the company or brands are communicated (Promotions)within this Promotions bucket the 'promotional mix' includes communication tools such as PR, advertising, sponsorship and others. Hence marketing influences the material aspects of a value chain through which products are designed, distributed and disposed of, as well as creating a significant 'brain print' impact on identities, culture and societal behaviour (Hurth & Whittlesea 2017). Viewed through that commercial lens, we contend that scientists are increasingly the 'marketers' within the academic 'business', engaging with press teams and PR departments but essentially responsible for the original design of research products, for making them accessible, and for communicating their worth.…”
mentioning
confidence: 99%
“…Decades of marketing research, and social/societal marketing practice in charities, social enterprises and other realms, has shown that the tools of marketing can be sharpened for sustainable wellbeing outcomes rather than profit maximisation (Kotler & Levy, 1969;Andreasen, 1994). As a result, marketing has been widely used to advance social change in the context of public health (Doner & Siegel 2004, Grier & Bryant 2005 and blueprints for how to reform the day-to-day practice of marketing to drive sustainability exist (Van Dam and Appeldorn, 1996;Beltz & Peattie, 2009;Peterson, 2012;Hurth et al 2015;Hurth & Whittlesea 2017), Given the growing recognition among geoscientists that meeting planetary challenges (UN Sustainable Development Goals, 2015 Paris Climate Agreement, Sendai Framework for Disaster Risk Reduction) will require radical new 'peoplecentred' approaches to science and technology, in order to promote large-scale behavioural change and adopt radical courses of collective action (FIGURE 2), might these radical considerations include bringing advanced, purpose-driven perspectives of marketing in as a potentially useful lens through which to view and shape the geoscience communication toolkit? FIGURE 2.…”
mentioning
confidence: 99%